Atopy, passive smoking, respiratory infections and asthma among children from kindergarten and elementary school - Ribeiro, Sandra Aparecida; Furuyama, Tatiana; Schenkman, Simone; Jardim, José Roberto de Brito (São Paulo Medical Journal, 2002)
CONTEXT: It has been demonstrated that children exposed to parents who smoke have more respiratory infections and asthma. OBJECTIVE: To study the association of both respiratory infections and asthma attacks with atopy, passive smoking and time spent daily at school, among children aged 4 to 9 years old from a kindergarten and elementary school in the city of São Paulo between May and July of 1996. TYPE OF STUDY: Descriptive study. SETTING: A kindergarten and elementary school with linkages to Universidade Federal de São Paulo/ Escola Paulista de Medicina. PARTICIPANTS: 183 children between 4 and 9 years old. MAIN MEASUREMENTS: A questionnaire consisting of 31 questions was answered by the parents of 183 children, and skin tests for inhaled antigens were performed on 88 children whose parents had given prior agreement for the procedure. RESULTS: Among the children, 51% had had respiratory infections during the preceding 3 months and 25.7% were asthmatic, of whom 52.1% had had one or more asthma attacks during the preceding 3 months. Children exposed to passive smoking did not have more respiratory infections or asthma attacks in comparison with those not exposed. We observed a significant association between atopic disorders in parents and children who were not exposed to passive smoking. There were also associations between atopic disorders in parents and asthma attacks in their infants, and between such disorders and a higher incidence of respiratory infections in the infants during the preceding 3 months. However, the presence of two or more positive skin tests for allergies did not have a correlation with respiratory infections and asthma attacks in this sample. In addition to this, children who studied full time at school did not have a higher occurrence of respiratory infections and asthma attacks. CONCLUSIONS: The presence of respiratory infections and asthma was associated with atopic parents but not with the presence of two or more positive skin tests for allergies among the children. Also, respiratory infections and asthma attacks were not associated with smoking parents or with the length of time spent by the children at school.